2017
DOI: 10.4081/aiua.2017.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of robotic and laparoscopic partial nephrectomy for small renal tumours

Abstract: Objective: To evaluate a single surgeon oncological and functional outcomes of laparoscopic partial nephrectomy (LPN) compared to robotic partial nephrectomy (RPN) for pT1a renal tumours. Results: There was no significant differences between the two groups with respect to patient gender, age, BMI, ASA score, tumours side, RENAL and PADUA scores. Mean operative time for RPN was 176 vs. 227 minutes for LPN (p = 0.001). Warm ischemia time was similar in both groups (p = 0.58). Estimated blood loss (EBL) was highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“… 7 Several studies have shown that surgeons can achieve better perioperative outcomes in kidney surgery when treating tumors with robot-assisted partial nephrectomy (RAPN), a technically easier procedure than LPN. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“… 7 Several studies have shown that surgeons can achieve better perioperative outcomes in kidney surgery when treating tumors with robot-assisted partial nephrectomy (RAPN), a technically easier procedure than LPN. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of surgical intervention for kidney cancer, patients with early T stage cancer would have a larger volume of healthy renal parenchyma for renal preservation, which might result in a better clinical outcome [ 20 ]. For partial nephrectomy, outcomes are more favorable for robotic surgery than for laparoscopic surgery in terms of a lower conversion rate to radical nephrectomy, favorable retention of renal function, and shorter warm ischemia time [ 21 23 ]. These features could partially explain the role of health expenditure in the MIR of kidney cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 6 These technical advances decrease the technical difficulty associated with the critical portion of PN, including tumor dissection and pelvicaliceal renal reconstruction. 7 …”
Section: Introductionmentioning
confidence: 99%